Laser interstitial thermal therapy is effective and safe for the treatment of brain tumors in NF1 patients after cerebral revascularization for moyamoya angiopathy: a report on two cases - Guida, Lelio; Beccaria, Kevin; Benichi, Sandro; Kossorotof, Manoelle; Naggara, Olivier; Bourgeois, Marie; Bourdeaut, Franck; Abbou, Samuel; Dangouloff-Ros, Volodia; Boddaert, Nathalie; Blauwblomme, Thomas (Frontiers in Neurology, 2023)
The co-occurrence of Moya Moya vasculopathy and extra-optic pathway tumors is rare in Neurofibromatosis (NF) type 1, with only 4 cases described in the literature. Brain surgery in these patients may be challenging because of the risk of brain infarction after skin and dural incision. Given its percutaneous and minimally invasive design, Laser Interstitial Thermal Therapy (LITT) is an ideal option for the treatment of brain tumors in these patients. Here, we report 2 patients with NF-1 and Moya Moya syndrome (MMS) treated for a brain glioma with LITT, after cerebral revascularization.The first patient, familial NF-1 had bilateral indirect revascularization with Multiple Burr Holes (MBH) for symptomatic MMS. Two years later, she was diagnosed with a left temporal tumor, with evidence of radiologic progression in 10 months. The second patient, familial NF-1 too, developed unilateral MMS when he was 6 y-o and was treated with MBH. At the age of 15 y, MRI showed a right cingular lesion, growing on serial MRIs. Both patients underwent LITT with no perioperative complication, they are progression free at 10 and 12 months, respectively, and tumors decreased in volume.If the association of extra optic neoplasm and Moyamoya angiopathy is seldomly reported in NF1, tumoral treatment is challenging both for avoiding stroke and achieving oncological control. Here, we show in 2 cases, that LITT could be a safe and effective option in these rare conditions.